2019
DOI: 10.56093/ijas.v89i11.95336
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics and determinants of farm household income in Bihar: evidence from panel data of selected villages

Abstract: The study is undertaken to analyze the farm household income, income sources, economic inequality, and determinants of income of farm households in Bihar which is based on five-year panel data (2010–11 and 2014–15). Findings of the study show that the income level of farm households in the selected villages of Bihar is low, but exhibited an impressive annual growth rate of 6% from 2010–11 to 2014–15. The income level showed a positive relation with the size of landholding. Further, the sources of house… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 1 publication
0
1
0
Order By: Relevance
“…In case of vegetables, lack of suitable storage facilities at reasonable charges and disorganized marketing system in the study area resulted in higher margin of retailers and higher share of marketing cost. The results are similar to the findings of Jadav et al (2011), Kumar et al (2008), Kumawat (2014 and2015) and Prasad (2001).…”
Section: Cost Margin and Price Spread In The Marketing Of Cabbagesupporting
confidence: 90%
“…In case of vegetables, lack of suitable storage facilities at reasonable charges and disorganized marketing system in the study area resulted in higher margin of retailers and higher share of marketing cost. The results are similar to the findings of Jadav et al (2011), Kumar et al (2008), Kumawat (2014 and2015) and Prasad (2001).…”
Section: Cost Margin and Price Spread In The Marketing Of Cabbagesupporting
confidence: 90%
“…Studies have shown that socioeconomic considerations influence Lambada marriages in metropolitan areas. Education, career prospects, and income levels have all influenced marriage dynamics in society (Kumar & Singh, 2019). Lambada marriage patterns in metropolitan areas show a confluence of tradition and modernity.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Mucuk and Sugözü (2011) suggested that EC in agriculture and industry had a positive impact on GDP, while EC in households and transportation had a negative impact. Differently, Kumar et al (2018) pointed out that there was unidirectional causality from electricity consumption to agricultural GDP in the longrun in India. In addition, Inumula et al (2020) explored that there was a causal linkage between agricultural GDP and gas consumption in India.…”
Section: Introductionmentioning
confidence: 99%